Employee Performance Determinants in Organizational Work Contexts: Faktor-Faktor Penentu Kinerja Karyawan dalam Konteks Kerja Organisasi - Ardelia Putri Devi Clarissa; Dewi Andriani; Vera Firdaus; Sumartik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Employee performance remains a central concern in organizational management due to its direct association with goal attainment and service quality. Specific Background Previous studies have emphasized leadership, communication, work environment, and organizational culture as key factors shaping employee performance across sectors. Knowledge Gap However, empirical evidence examining these variables simultaneously within specific organizational contexts remains limited. Aims This study aims to analyze the relationships between organizational factors and employee performance within the selected research setting. Results The findings indicate that leadership practices, communication patterns, and work-related conditions demonstrate statistically supported relationships with employee performance. Novelty The study offers contextual empirical evidence by integrating multiple organizational variables within a single analytical framework applied to a localized organizational setting. Implications These results provide practical insights for organizational managers in formulating policies related to human resource management while also contributing to the enrichment of empirical literature on employee performance determinants. Keywords: Employee Performance, Leadership, Communication, Work Environment, Organizational Culture Key Findings Highlights: Multiple organizational factors show measurable associations with employee outcomes Managerial practices are contextually linked to work behavior patterns Organizational conditions remain central to performance-related evaluations